(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The geodiversity of Indonesia as an archipelago country has contributed huge benefits to the development of geotourism. One of them is featured as Pindul Cave geosite in Gunung Kidul Yogyakarta, which is already running as a well-known tourism site within the Gunung Sewu Geopark. In order to create a sustainable geotourism, it is necessary to have a good hazard risk management, especially regarding to geohazards. Since Pindul Cave has not prepared the management yet, this study aims to assess the variables in the geosite, this includes the likelihood and consequences, that will provide a holistic risk management plan. The highest geohazard risk comes from floods and landslides on the geosite. The assessment result mentioned that Pindul Cave Geosite is included in the High-Extreme category, which means that geosite needs immediate repairing action and even requires a specific plan on the managerial level in terms of handling and emergency conditions. In dealing with such risks, it is necessary to have engineering, administrative control, and procurement of personal protective equipment (PPE).